Driving of Outer Belt Electron Loss by Solar Wind Dynamic Pressure Structures: Analysis of Balloon and Satellite Data. Issue 12 (7th December 2020) - Breneman, A. W.; Halford, A. J.; Millan, R. M.; Woodger, L. A.; Zhang, X.‐J.; Sandhu, J. K.; Capannolo, L.; Li, W.; Ma, Q.; Cully, C. M.; Murphy, K. R.; Brito, T.; et al.
Abstract: We present observations of ~10–60 min solar wind dynamic pressure structures that drive large‐scale coherent ~20–100 keV electron loss from the outer radiation belt. A combination of simultaneous satellite and Balloon Array for Radiation‐belt Relativistic Electron Losses (BARREL) observations on 11–12 January 2014 shows a close association between the pressure structures and precipitation as inferred from BARREL X‐rays. Specifically, the structures drive radial ExB transport of electrons up to 1 Earth radii, modulating the free electron energy available for low‐frequency plasmaspheric hiss growth, and subsequent hiss‐induced loss cone scattering. The dynamic pressure structures, originating near the Sun and commonly observed advecting with the solar wind, are thus able to switch on scattering loss of electrons by hiss over a large spatial scale. Our results provide a direct link between solar wind pressure fluctuations and modulation of electron loss from the outer radiation belt and may explain long‐period modulations and large‐scale coherence of X‐rays commonly observed in the BARREL data set. Plain Language Summary: The Earth's low‐density magnetosphere is a region of enclosed magnetic field lines that contains energetic electrons ranging from eV to MeV energies. These populations can be greatly enhanced in response to solar driving. Following enhancements, energetic electron populations are depleted on timescales of hours to days by various processes. One important depletion process occurs when an electromagnetic plasma wave called plasmaspheric hiss, which exists within a high plasma density region called the plasmasphere and its (occasional) radial extension called the plume, scatters energetic electrons into the atmosphere. In this paper, we show that these hiss waves can be switched on by compressions of the magnetosphere which occur in response to ~1 hr long pressure structures in the solar wind. These structures originate at or near the Sun and are very common in the solar wind at 1 AU. The newly excited hiss waves scatter electrons into the atmosphere where they are observed on balloon‐borne X‐ray detectors. Our results suggest that magnetospheric models that predict the loss of electrons from hiss waves may be improved by consideration of solar wind pressure‐driven dynamics. Key Points: We report on large‐scale driving of electron precipitation from outer belt by commonly observed ~1 hr duration solar wind pressure structures The resulting forced breathing of magnetosphere causes ExB drift which modulates population of tens of keV electrons These electrons trigger growth of hiss waves which, in turn, modulate precipitation loss observed as X‐rays on BARREL